The impact of food prices on poverty and food security - Headey, Derek D.; Martin, Will (Annual Reviews, 2016)
Recent food price fluctuations have sparked renewed interest in the impact of food prices on poverty and food security. This paper reviews the literature and analyzes why different authors often reach different conclusions regarding the welfare impacts of food price changes. We first show that systematic measurement errors in household surveys may seriously affect estimates of the poor's dependence on food purchases at any given point in time. We then turn to the theoretical case for why the rural poor might ultimately benefit from higher food prices, with a particular focus on agricultural supply responses and resultant increases in demand for unskilled farm labor, which raise the wages of the poor. Consistent with these predictions, more sophisticated simulation models and new econometric evidence suggest that sustained increases in food prices have often benefited the poor and likely contributed to faster global poverty reduction from the mid-2000s onward. Conversely, the recent decline in agricultural prices could retard global poverty reduction.